SCALING BLENDED APPROACHES IN TEACHER PROFESSIONAL DEVELOPMENT: A MODEL FOR EMPOWERING TEACHERS IN UNDER-RESOURCED CONTEXTS - Phuong Thao, Nguyen (HNUE Journal of Science: Journal of Educational Science, 2025)
Blended approaches, which typically combine technology-enhanced learning with in-person professional development, have gained traction in teacher professional development (TPD) as a scalable approach to improving teaching quality, particularly in under-resourced contexts. However, despite its promise, there remains a lack of integrated frameworks specifically designed to guide the sustainable and context-sensitive scaling of blended TPD. This paper proposes the SCALE-BTPD model which synthesizes key insights from existing scalability models and blended learning literature. The model consists of three interdependent layers: Enabling Conditions, Blended Learning Pathways, and an Iterative Scaling Mechanism. SCALE-BTPD reframes scale as a dynamic, equity-centered process rooted in local realities and teacher agency. It suggests practical guidance for policymakers, education leaders, and implementers seeking to design and scale blended TPD systems that are responsive, inclusive, and oriented toward long-term institutional change.